Sociolegal Analysis of the Rawa Pening Agrarian Conflict as an Effort to Legally Protect Land Rights - Febryana Maharani (Semarang State University Undergraduate Law and Society Review, 2025)
Land is a fundamental asset that plays a vital role in supporting community welfare and livelihoods. In the Rawa Pening area, a significant agrarian conflict has arisen due to a lake revitalization project initiated by the government, involving the National Land Agency (BPN), the Indonesian National Armed Forces (TNI), and the Ministry of Public Works and Housing (PUPR). The project, aimed at flood and sediment control, has led to the displacement of farmers and fishermen, disrupting agricultural lands and residential areas. Despite possessing legal land certificates, residents claim that boundary markers placed for the project have encroached upon their property, indicating a lack of adequate legal protection. This study aims to analyze the legality of land acquisition procedures and their alignment with existing regulations. The research employs a normative and empirical juridical approach, combining legal document analysis and field interviews. The findings reveal that land acquisition was carried out with minimal community involvement, potentially violating procedural requirements and leading to legal uncertainty and possible human rights violations. The study identifies the need for a fair and transparent land acquisition process that respects property rights and provides legal certainty for affected communities. It concludes that stronger enforcement of agrarian laws and community participation are essential to resolving land conflicts and ensuring equitable development outcomes.